A pyrylium–coumarin dyad as a colorimetric receptor for ratiometric detection of cyanide anions by two absorption bands in the visible region. (29th October 2015) - Shiraishi, Yasuhiro; Nakamura, Masaya; Matsushita, Naoyuki; Hirai, Takayuki
Abstract : A pyrylium–coumarin dyad behaves as a colorimetric receptor for ratiometric detection of cyanide anions in aqueous media by two absorption bands in the visible wavelength region. Abstract : We synthesized a pyrylium–coumarin dyad (1 ) and used it for colorimetric detection of cyanide anions (CN − ) in aqueous media. The receptor itself exhibits a long-wavelength absorption band at 643 nm due to the strong intramolecular charge transfer (ICT) from the diethylaminocoumarin to the pyrylium moiety. Selective nucleophilic addition of CN − to the pyrylium ring triggers the ring cleavage rapidly (within 8 min). This suppresses the ICT and decreases the intensity of the 643 nm band, along with an appearance of a new shorter-wavelength band at 472 nm assigned to the π, π* transition of the diethylaminocoumarin moiety. This drastic absorption change (643 nm → 472 nm) facilitates ratiometric detection of CN − based on the intensities of these two absorption bands in the visible region and successfully detects CN − as low as 8 μM.